الأنثروبولوجياالثقافيةوالإنتاج المعرفي العربي - ساسي, سفيان (Changement Social, 2018)
women'smovement in Anthropology, whichemerged in an exceptionalway in the second half of the twentiethcentury in the westthroughstudies in the anthropology type related issues, by researchers in time academies have betrun in the fieldisconfined to men, the field of science and research and continues with the rudimentarysocietiescharacterized, although the betwasrisky, in view of the absence of acceptable to the poles in the creation of anthropologicalknowledge or related branches, but theymanaged to someextent to put theirstudies, theirideas and vision in the THORNY research issues, reflect the desire, the ability and effort in the sector in the field of anthropology, if thiswas the situation for women in the world whodescribed the freedom and the emancipation of women, whatis the case for womensubject to the peculiarities of the Maghreb: culture, Religion, beliefs and traditions?